Do I know more than my body can tell? An Empirical Analysis of Private Information - Amelie C. Wuppermann (Verein für Socialpolitik, 2010)
Economic theory stresses the importance of adverse selection in competitive insurance markets. The empirical evidence for adverse selection in different health-related insurance markets, however, is mixed. This study evaluates whether different degrees of private information left after different underwriting processes could explain these findings. The analysis uses data from the English Longitudinal Study of Ageing, one of the rare longitudinal data sets with objectively measured health information. Using self-rated health as a proxy for private information this study finds that thorough underwriting eliminates private information on health risks and thus the scope for adverse selection in life and health insurance.
Keywords: I10; D82; C33; 330; ELSA; self-rated health; adverse selection; objective health measures